2015
DOI: 10.1016/j.ijpharm.2015.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Development of multifunctional lipid nanocapsules for the co-delivery of paclitaxel and CpG-ODN in the treatment of glioblastoma.

Abstract: In this work, multifunctional lipid nanocapsules (M-LNC) were designed to combine the activity of the cytotoxic drug paclitaxel (PTX) with the immunostimulant CpG. This nanosystem, consisting of modified lipid nanocapsules coated with a cationic polymeric shell composed of chitosan (CS), was able to allocate the hydrophobic drug PTX in the inner oily core, and to associate onto the surface the genetic material CpG. The CS-coated LNC (CS-LNC), showed a narrow size distribution with an average size of 70 nm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…All the systems were treated with drugs and nanoparticles diluted with serum free N1 supplemented medium. Serum free N1 supplemented medium was prepared with DMEM with amino acids, 1% antibiotics (10,000 units penicillin, 10 mg streptomycin, 25 μg amphotericin B/mL solubilized in an appropriate citrate buffer), 1% HEPES buffer, 1% NEAA (Non Essential Amino Acid) 100X, 1% sodium pyruvate, 1% N1 medium supplement 100X [33,34]. Cell viability reduction assay was performed using CellTiter 96® AQueous One Solution cell proliferation assay kit containing a tetrazolium compound [3- Evaluation of HMGB1 secretion and ATP release upon incubation of DACHPt-loaded nanoparticles with B6KPC3 cells B6KPC3 cells were plated and treated as described above, with increasing concentrations of DACHPt-loaded NP, oxaliplatin and DACHPt water solution during 24 h. Blank NP were also tested as a control.…”
Section: Viability Studies On B6kpc3 A549 and Ht-29 Cell Linesmentioning
confidence: 99%
“…All the systems were treated with drugs and nanoparticles diluted with serum free N1 supplemented medium. Serum free N1 supplemented medium was prepared with DMEM with amino acids, 1% antibiotics (10,000 units penicillin, 10 mg streptomycin, 25 μg amphotericin B/mL solubilized in an appropriate citrate buffer), 1% HEPES buffer, 1% NEAA (Non Essential Amino Acid) 100X, 1% sodium pyruvate, 1% N1 medium supplement 100X [33,34]. Cell viability reduction assay was performed using CellTiter 96® AQueous One Solution cell proliferation assay kit containing a tetrazolium compound [3- Evaluation of HMGB1 secretion and ATP release upon incubation of DACHPt-loaded nanoparticles with B6KPC3 cells B6KPC3 cells were plated and treated as described above, with increasing concentrations of DACHPt-loaded NP, oxaliplatin and DACHPt water solution during 24 h. Blank NP were also tested as a control.…”
Section: Viability Studies On B6kpc3 A549 and Ht-29 Cell Linesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Thus, Liu et al 4 showed that chitosan surface-modified poly(lactideco-glycolide)-chitosan nanoparticles (PLGA/CS NPs) loaded with carmustine (bis-chloroethylnitrosourea, BCNU) and its sensitizer (O 6 -benzylguanine, BG) had a strong antitumor effect in the F98 glioma-bearing mice model. In another study by Lollo et al, 11 the authors could demonstrate similar effects with paclitaxel (PTX)-loaded particles in GL261 gliomabearing mice. Subsequent functionalization of the chitosan nanoparticle surface with bioligands further enhanced the ability of the particles to cross the blood-brain barrier (BBB) and their brain tumor accumulation level.…”
Section: Introductionmentioning
confidence: 80%
“…Many pre-clinical studies adapted CED to infuse nano-formulations directly into the brain [59]. C57BL/6 J mice were used to infuse a 10 μL solution of lipid nanocapsules (LNCs) having an average size of 70 nm into their skull at an infusion rate of 0.5 μL/min [60]. An alternate method for direct infusion was also reported in which drug-loaded micelles were injected by making small incisions on the skull.…”
Section: Alternate Routes and Strategies 61 Conventional Enhanced Dementioning
confidence: 99%